Efficacy and safety of anakinra for the treatment of rheumatoid arthritis: an update of the Oregon Drug Effectiveness Review Project - Kylie Thaler (Dove Medical Press, 2009)
Kylie Thaler1, Divya V Chandiramani2, Richard A Hansen2, Gerald Gartlehner11Department for Evidence-based Medicine and Clinical Epidemiology, Danube University Krems, Krems, Austria; 2UNC Eshelman School of Pharmacy, University of North Carolina at Chapel Hill, Chapel Hill, NC, USAObjective: To systematically review the general and comparative efficacy and safety of anakinra for rheumatoid arthritis.Methods: We searched MEDLINE®, Embase, The Cochrane Library, and the International Pharmaceutical Abstracts from 1980 to April 2009. We manually searched reference lists of pertinent review articles and explored the Center for Drug Evaluation and Research database. For efficacy we included randomized controlled trials (RCTs) comparing anakinra with placebo or other biologics. For safety both experimental and observational studies were eligible. Two persons independently reviewed abstracts and full text articles and extracted relevant data.Results: We included data from 3 RCTs comparing anakinra with placebo for rheumatoid arthritis (RA). The pooled relative risk (RR) of an ACR50 (American College of Rheumatology) response for anakinra compared with placebo is 2.28 (95% CI 1.41 to 3.67). Adjusted indirect comparisons of ACR50 response rates of anakinra and anti-TNF agents showed a RR of 0.67 (95% CI 0.38 to 1.17) favoring the anti-TNF drugs. This result did not reach statistical significance. For safety, we included 9 experimental and observational studies of 24 weeks to 3 years duration. Up to 30% of patients withdrew from the studies due to adverse events. 67.2% (95% CI 38.7 to 95.7) of patients experienced an injection site reaction.Conclusions: Anakinra is an effective drug for treating RA. Indirect comparisons with adalimumab, etanercept and infliximab, however, showed a trend towards greater efficacy for the anti-TNF drugs. Anakinra also seems to be associated with comparably high rates of injection site reactions. These results should be taken into account when considering biologic therapy for patients with RA.Keywords: anakinra, rheumatoid arthritis, infection